2022
DOI: 10.1136/bmjopen-2021-059411
|View full text |Cite
|
Sign up to set email alerts
|

Understanding national trends in COVID-19 vaccine hesitancy in Canada: results from five sequential cross-sectional representative surveys spanning April 2020–March 2021

Abstract: ObjectiveTo examine rates of vaccine hesitancy and their correlates among Canadian adults between April 2020 and March 2021.DesignFive sequential cross-sectional age, sex and province-weighted population-based samples who completed online surveys.SettingCanada.ParticipantsA total of 15 019 Canadians aged 18 years and over were recruited through a recognised polling firm (Leger Opinion). Respondents were 51.5% female with a mean age of 48.1 (SD 17.2) years (range 18–95 years) and predominantly white (80.8%).Pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 61 publications
1
48
1
1
Order By: Relevance
“…Most studies used samples of adults ( N = 26). Sixteen studies addressed vaccine hesitancy (i. e., doubts concerning the reception of a COVID‐19 vaccine) 6 , 7 , 8 , 16 , 17 , 29 , 33 , 34 , 37 , 39 , 44 , 45 , 46 , 47 , 48 , 50 and 14 studies explored vaccine unwillingness (i.e., the likelihood of refusing a COVID‐19 vaccine). 28 , 30 , 32 , 35 , 36 , 38 , 40 , 41 , 42 , 43 , 46 , 49 , 51 , 52 The characteristics of the studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies used samples of adults ( N = 26). Sixteen studies addressed vaccine hesitancy (i. e., doubts concerning the reception of a COVID‐19 vaccine) 6 , 7 , 8 , 16 , 17 , 29 , 33 , 34 , 37 , 39 , 44 , 45 , 46 , 47 , 48 , 50 and 14 studies explored vaccine unwillingness (i.e., the likelihood of refusing a COVID‐19 vaccine). 28 , 30 , 32 , 35 , 36 , 38 , 40 , 41 , 42 , 43 , 46 , 49 , 51 , 52 The characteristics of the studies are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Twelve papers reported the prevalence of COVID‐19 vaccine hesitancy among Canadians. 6 , 7 , 8 , 16 , 17 , 33 , 37 , 39 , 45 , 47 , 48 , 50 The pooled prevalence of COVID‐19 vaccine hesitancy was 42.3% (95% CI, 33.7%−51.0%, Figure 2 ). The heterogeneity level in the analysis was high ( I 2 = 99.03%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another Canadian-wide survey, which examined COVID-19 vaccine intention at the beginning of COVID-19 vaccine rollout, reported that only 9% of respondents indicated that would not receive a COVID-19 vaccine [21] , indicating intention to receive a COVID-19 vaccine may have continued to increase as COVID-19 vaccine rollout commenced. In contrast, vaccine hesitancy toward a COVID-19 vaccine, measured during the same period in another Canadian population, was lowest at the beginning of the pandemic, and increased throughout the summer and fall of 2020, before experiencing a sharp decline in vaccine hesitancy in November 2020 [22] . In BC, as COVID-19 vaccine programs continue, reported vaccine receipt has outpaced initial estimated vaccine intention, with >90% of eligible adolescents (12+ years of age) and adults having received at least 1 dose of COVID-19 vaccine, prior to the pediatric (5–11yearsold) COVID-19 vaccine approval announcement in November 2021 [23] .…”
Section: Discussionmentioning
confidence: 85%